Bird Species Based On Altitudinal Zonation On Mount Kerinci Hiking Trail Through Kersik Tuo - Lintang Yodhy; Rizaldi Rizaldi; Wilson Novarino (Jurnal Biologi Universitas Andalas, 2022)
Altitudinal gradient has specific factors that affect the composition of the bird community. A study of bird species based on altitude zonation on the Mount Kerinci hiking trail through Kersik Tuo, Kerinci, Jambi was conducted in August 2021 to know how the composition and structure of bird communities differed based on altitude zonation. This study was conducted using the point-count method. Point-count distributed along the hiking trail from 1,755 to 2,906 m asl and included in three zones (Zone I: 1,755 - 1,900 m asl: Zone II: 1,901 - 2,500 m asl: and Zone III: above 2,501 m asl). Four hundred sixty-seven individuals from 78 species of birds were recorded along the hiking trail. This number indicates that the number of bird species in the study at Mount Kerinci was more than the number of bird species in the study at other mountains in Sumatra. Species richness was the highest in Zone I (54 species), followed by Zone II (34 species) and Zone III (20 species). The species richness decrease as elevation increases.